WLE/ICRISAT integrates smart water management tools and Innovation Platforms in small-scale Zimbabwean irrigation schemes to deliver enhanced water productivity, incomes, and conflict reduction - CGIAR Research Program on Water, Land and Ecosystems (2019)
The combined use of Agricultural Innovation Platforms and smart water management tools in two small-scale communal irrigation schemes in Zimbabwe, resulted in major improvements in water and land productivity, household incomes, and reductions in conflict levels. As a result, the Director of Irrigation with support from the Australian Council for International Agricultural Research (ACIAR) agreed to fund a second project that is extending the model to 30 more irrigation schemes, covering 757 ha and 1698 farmers.